"Via-Less” UWB Filter using Patched Microstrip Stubs - Mohammad Shahrazel, Razalli; Alyani, Ismail; Mohamed Adzir, Mahdi; Mohd Nizar, Hamidon (VSP (imprint of Brill), 2009)
Link to publisher's homepage at http://www.ingentaconnect.com/content/vsp/jew